Small angle x-ray scattering to investigate the specific surface of hydrated alginate microbeads. (June 2022) - Ghernaouti, F.; Perrin, A.; Causse, J.; Chandre, F.; Cornu, D.; Cambedouzou, J.
Abstract: Encapsulation of active substances in biopolymer beads becomes a widely developed approach to gain efficiency for many applications. However, the characterization of such aqueous materials in their early stage of production is very delicate regarding their textural properties. The classical tools such as gas adsorption and Hg porosimetry can hardly provide relevant information since they require the removal of water, which is yet a fundamental part of the sample that drives its structure. In this article, we used small angle x-ray scattering (SAXS) as a tool in order to determine the specific surface area (SSA) of alginate microbeads in solution. This has been made possible by a careful procedure of SAXS measurements, involving calibration samples, allowing writing intensities in absolute units. Therefore, the Porod limit theory was used to calculate the SSA from the scattering length contrast and the measured absolute intensity. In addition, we compared the SSA of microbeads obtained from pure water and from a widely used cell culture medium, and we followed the textural evolution of a water alginate sample during the first step of a gentle drying process. Our results show that SAXS should be considered as a valuable tool for physico-chemists and food formulators in order to extract in situ dimensional and textural information of hydrogels during the formulation. It enables them to figure out the real surface available for the sorption of additive or active molecules in the formulation of biopolymers such as alginates, empowering them to better control encapsulation processes. Graphical abstract: Image 1 Highlights: Specific surface area of fully hydrated alginate microbeads can be measured by SAXS. Specific surface area of hydrated alginates beads is much lower than of dried ones. Drying increases specific surface of alginate beads through microporosity growth.